COMPETITIVENESS OF LEADING COMMODITIES TO SUPPORT DEVELOPING REGION OF AGROTOURISM - Murwatiningsih Murwatiningsih; Dyah Maya Nihayah; Shanty Oktavilia (Economic Journal of Emerging Markets, 2013)
Abstract